Pengaruh Citra Merek, Pengalaman Konsumen, dan Word of Mouth Terhadap Niat Beli Ulang (Studi Pada Konsumen KFC di Kota Semarang) - Ika Nur Khikmatul Aini; R.A Marlien; Alimuddin Rizal Riva’i (Jurnal Mirai Management, 2022)
Abstract This research was conducted with the intention of testing and analyzing the influence of brand image, customer experience, and word of mouth on repurchase intention. The object of this research is Kentucky Fried Chicken (KFC) consumers in the city of Semarang. This study uses a purposive sampling method with a minimum age of 17 years for respondents, and the total sample used is 100 respondents. Survey method through the distribution of questionnaires used in the study. Multiple linear regression analysis technique was used in this study. The results obtained in this study partially show that the variables of brand image, customer experience, and word of mouth have a positive and significant influence on repurchase intention. Keywords: Brand Image, Customer Experience, Word of Mouth, and Repurchase Intention